Developing booklet of "vegetables aquaponic": Improving knowledge, interest of consumption and motivation of vegetable cultivation - Supriyatin; Rahayu, Sri; Fitriasih, Fajarani; Yanuar, Rizki Aditya; Fadillah, Taufik Ismail (Biosfer: Jurnal Pendidikan Biologi, 2024)
Lack of public knowledge, interest, and motivation regarding the benefits of vegetables as well as the development of vegetable cultivation techniques that are easy to apply on limited land have resulted in low levels of daily vegetable consumption. One effort to overcome the low consumption of vegetables is to increase knowledge about nutrition and nutrition contained in them by using booklet media. This research aims to develop a booklet with an attractive and easy-to-understand design, to increase interest in consuming and motivation to cultivate vegetables. Based on the results of media and material expert feasibility tests, the aquaponics booklet obtained a result of 92% in the very suitable category, while user testing in the development process obtained a result of 94% in the very suitable for use category. Based on the results of the t test, the 2-tailed Sig value was 0.009 <0.05, which means there was a significant increase in knowledge about vegetables after participants took part in aquaponics training. The results of the correlation test show that there is a high and positive relationship between interest in consuming vegetables and motivation to grow vegetables with a correlation of 0.676. Thus, it can be concluded that the vegetable aquaponics booklet has met the feasibility based on user testing and can increase knowledge, consumption interest, and motivation to grow vegetables..